PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN WANA WISATA GONOHARJO PERUM PERHUTANI UNIT I JAWA TENGAH - Sapta Utama; Agus Hermani; Wahyu Hidayat (Jurnal Ilmu Administrasi Bisnis, 2013)
Companies that are able to compete in the markets are the company that provides quality products or services. So the company is expected to continue to make improvements, especially on quality of products and services. Companies also need to seek advice service to give the best to their customers. This requires the identification of the main determinants of service quality from the perspective of the consumers. This study aims is to determine the quality of product and service quality Wana Wisata Gonoharjo and to investigate the effect of product quality and service quality on customer satisfaction Wana  Wisata Gonoharjo. This type of research is explanatory, to explain the causal relationship between the variables of quality products or services on customer satisfaction. Its population is Wana Wisata Gonoharjo’s visitors, the number of samples in this study amounted to 100 people. The sampling on this study is used ‘Accidental sampling’ method. Data collection methods used is literature studies, observation and questionnaires. Data analysis in this study is qualitative and quantitative analysis using validity, reliability testing, cross tables, simple linear regression, multiple linear regression, T test and F test and the coefficient of determination. Based on the data analysis and simultaneously partial quality products or services has a positive impact on customer satisfaction variables Wana Wisata Gonoharjo Kendal. Partially, the influence of product quality to customer satisfaction is at 47.3%. The effect of service quality on customer satisfaction is 40.2%. Simultaneously, the influence of product quality and service quality on customer satisfaction is 55.2%. To improve customer or visitors satisfaction of Wana Wisata Gonoharjo, superintendent should be able to improve product and service quality provided to the customer, with the addition of variants attractions like water boom or improved services.